About 3.8 hours, if asking for a whole number round to 4
Answer:
y = 5
Step-by-step explanation:
if y = 5 then
(√10-1) -1 = 2
3 - 1 = 2
true
Answer:
7/12 in exact form
Step-by-step explanation:
I think you just multiply the numerator by the resipical of the denominator.
Step-by-step explanation:
factor 4 out of the variable terms, as this helps.
but my approach is simply to define the target and then calculate "backwards".
we want to find
(ax + b)² = a²x² + 2abx + b²
and now we compare with the original equation :
a²x² = 4x²
a² = 4
a = 2
2abx = 16x
2×2×bx = 16x
4b = 16
b = 4
b² = 16, but we have only 3, so we need to subtract 16-3 = 13 from the completed square.
so, our equation is
(2x + 4)² - 13 = 0
(2x + 4)² = 13
2x + 4 = sqrt(13)
2x = sqrt(13) - 4
x = sqrt(13)/2 - 2
Answer:
-228
Step-by-step explanation:
I Used the given functions to set up and simplify f(-6)
Hope this helps:)